Limited Substrate Specificity of PS/γ-Secretase Is Supported by Novel Multiplexed FRET Analysis in Live Cells - Mei C. Q. Houser; Yuliia Turchyna; Florian Perrin; Lori Chibnik; Oksana Berezovska; Masato Maesako (Biosensors, 2021)
Presenilin (PS)/γ-secretase is an aspartyl protease that processes a wide range of transmembrane proteins such as the amyloid precursor protein (APP) and Notch1, playing essential roles in normal biological events and diseases. However, whether there is a substrate preference for PS/γ-secretase processing in cells is not fully understood. Structural studies of PS/γ-secretase enfolding a fragment of APP or Notch1 showed that the two substrates engage the protease in broadly similar ways, suggesting the limited substrate specificity of PS/γ-secretase. In the present study, we developed a new multiplexed imaging platform that, for the first time, allowed us to quantitatively monitor how PS/γ-secretase processes two different substrates (e.g., APP vs. Notch1) in the same cell. In this assay, we utilized the recently reported, spectrally compatible visible and near-infrared (NIR)-range Förster resonance energy transfer (FRET) biosensors that permit quantitative recording of PS/γ-secretase activity in live cells. Here, we show that, overall, PS/γ-secretase similarly cleaves Notch1 N100, wild-type APP C99, and familial Alzheimer’s disease (FAD)-linked APP C99 mutants in Chinese hamster ovary (CHO) cells, which further supports the limited PS/γ-secretase substrate specificity. On the other hand, a cell-by-cell basis analysis demonstrates a certain degree of variability in substrate recognition and processing by PS/γ-secretase among different cells. Our new multiplexed FRET assay could be a useful tool to better understand how PS/γ-secretase processes its multiple substrates in normal and disease conditions in live, intact cells.